PENATALAKSANAAN FISIOTERAPI PADA KONDISI POST OPERASI FRAKTUR SUPRACONDYLER HUMERI SINISTRA DENGAN PEMASANGAN NAIL AND WIRE - Eko Budi Prasetyo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Many found case of Fractur supracondyler humeri sinistra which caused by accident  and its  elbow   used for  the  antiers  to  heavy the  body.  This  condition  will  generate the  problems  of physical capacities in the form of pain in bone, spasme of muscle and limitation of LGS. As for functional  ability  problems  difficulty  of  moment  for    activity  toileting,  treatment  of  everyday activity and x'self entangling  arm of fraktur. Research method used by case study. After get the treatment  in  therapy  during  6x  therapy  (  T1-T6)  with  the  Infra  Red,  Massage,  Therapy  of Practice and TENS getting a well enough result. As for its  therapy is degradation assess the pain in bone kept quiet from value 2 becoming value 1, pain in bone depress from value 4 becoming value  2  and  pain  in  bone  move  from  value  6  becoming  value  5,spasme  muscle  decrease  from value 2 becoming value 1, active improvement LGS  area sagital from S = 50-00-900 becoming S = 50-00-1000 and area of giration R ( s900) = 800-00-750 becoming R ( s900) = 900-00-800, passive improvement LGS [at] area of sagital S = 50-00-1100 becoming S = 100-00-1200 area of giration R  (  s900)  =  850-00-850 becoming  R  (  s900)  =  950-00-850.  Make-Up  of  value  ADL  of  dressy activity  from  value  2  becoming  value  1,  cleaning  from  value  3  becoming  value  2,  bath  from value  2  becoming  value  1,  using  toilet  from  value  2  becoming  value  1,  dressing  smartly  from value 2 becoming value 1 and prepare to drink from value 2 becoming value 1.Key  Word  :  Fractur supracondyler  humeri  sinistra,  Infra  Red,  Massage,  aktif  and  pasif movement, Hold Relax dan TENS.